Caloric Restriction Diet Induces Specific Epigenotypes Associated with Life Span Extension - Bozhkov, A. I.; Nikitchenko, Yu. V. (Journal of Nutritional Therapeutics, 2013)
The lifespan of Wistar rats on caloric restriction diet (CRD) is correlated with the changes in prooxidant-antioxidant balance, in the contents of triiodothyronine, and thyroxin (epigenotype characteristics). It has been shown that in a month after the moment of one-month-old rats began to receive CRD the part (up to 15 %) of experimental animals died without any apparent cause, irrespective of the degree of calorie restriction (40 %, 57 % and 60 % weight-loss). The rest of animals with 40 %, 57 % and 60 % weight-loss had longer life span in comparison with control group. The CRD-induced life-span prolongation in animals was accompanied by the induction of specific epigenotypes featured by acceleration of the electron transfer rate in electron transport chain and subsequent reduced production of reactive oxygen species and increased antioxidant activity. The activity of glutathione reductase, glutathione transferase, NADH-cytochrome C reductase, isocitrate dehydrogenase was elevated. The activity of Se-dependent glutathione peroxidase was higher more than 30 times as compared with control. Likewise, the epigenotypes of animals with 40 %, 57 % and 60 % weight-loss CR, were characterized by 37, 43 and 56 % decrease in triiodothyronine and 50, 25, 39 % decrease in tyrosine, respectively. The observed induction of specific epigenotypes is associated with higher life-span and is related to the multivariant metabolic strategies of adaptation to CRD.